2010
DOI: 10.1308/003588410x12518836440045
|View full text |Cite
|
Sign up to set email alerts
|

Training in the practical application of damage control and early total care operative philosophy – perceptions of UK orthopaedic specialist trainees

Abstract: INTRODUCTION Despite improvements in the outcome of individuals sustaining significant injury, the optimum management of fractures in traumatised patients remains an area of debate and publication. There is, however, a paucity of studies regarding the specifics of acquired experience and training of junior orthopaedic surgeons in the practical application of these skills. Our null hypothesis is that, despite alteration in surgical training, the perceived confidence and adequacy of training of UK orthopaedic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…This may relate to the low familiarity of UK trainees with the concept and the fact that it is not performed often. A 2010 survey of 232 UK Orthopaedic Trainees revealed that over 2/3 of trainees surveyed had no confidence in their ability to pack a pelvis and 60% had never even seen a case (5). In a more complicated cases of spanning external fixation for a 'floating knee, trainees also reported a decreased level of perceived confidence and limited exposure to the technique.…”
Section: Discussionmentioning
confidence: 99%
“…This may relate to the low familiarity of UK trainees with the concept and the fact that it is not performed often. A 2010 survey of 232 UK Orthopaedic Trainees revealed that over 2/3 of trainees surveyed had no confidence in their ability to pack a pelvis and 60% had never even seen a case (5). In a more complicated cases of spanning external fixation for a 'floating knee, trainees also reported a decreased level of perceived confidence and limited exposure to the technique.…”
Section: Discussionmentioning
confidence: 99%
“…In der Unfallchirurgie sowie Orthopä-die ist weltweit das DCS-Prinzip zentraler Ausbildungsinhalt und schon zu einem frühen Ausbildungsstand bekannt [12]. Dadurchsind Unfallchirurgenmit prioritätenbezogener Diagnostik und Therapie auf Basis von Schadensbegrenzung und "treat first what kills first" im Schockraum vertraut [17].…”
Section: Damage Control Surgeryunclassified
“…1 Swiftly assembled, simple, reliable constructs are paramount, especially in mass casualty situations 2 and for trainees given limited exposure to this situation. 3 …”
Section: Ann R Coll Surg Engl 2013; 95: 437-447mentioning
confidence: 99%